2021
DOI: 10.1038/s41467-021-22753-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurexins regulate presynaptic GABAB-receptors at central synapses

Abstract: Diverse signaling complexes are precisely assembled at the presynaptic active zone for dynamic modulation of synaptic transmission and synaptic plasticity. Presynaptic GABAB-receptors nucleate critical signaling complexes regulating neurotransmitter release at most synapses. However, the molecular mechanisms underlying assembly of GABAB-receptor signaling complexes remain unclear. Here we show that neurexins are required for the localization and function of presynaptic GABAB-receptor signaling complexes. At fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…Initial studies of individual or combined deletions of Nrxn1α, Nrxn2α, and Nrxn3α in mice (with retained expression of β-neurexins) revealed that α-neurexins are essential for synaptic transmission and survival, and that their combined deletion causes a decrease in release probability but does not induce major changes in excitatory synapse numbers (32)(33)(34). These studies showed that the deletions of α-neurexins lower the activity of presynaptic voltage-gated Ca 2+ channels, a finding that was extended in subsequent studies to deletions of all α-and β-neurexins (35)(36)(37).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Initial studies of individual or combined deletions of Nrxn1α, Nrxn2α, and Nrxn3α in mice (with retained expression of β-neurexins) revealed that α-neurexins are essential for synaptic transmission and survival, and that their combined deletion causes a decrease in release probability but does not induce major changes in excitatory synapse numbers (32)(33)(34). These studies showed that the deletions of α-neurexins lower the activity of presynaptic voltage-gated Ca 2+ channels, a finding that was extended in subsequent studies to deletions of all α-and β-neurexins (35)(36)(37).…”
Section: Introductionmentioning
confidence: 81%
“…Following the procedures previously described in ( 56 ), dSTORM images were recorded with a Vutara SR 352 (Bruker Nanosurfaces Inc., Madison, WI) commercial microscope based on single-molecule localization biplane technology ( 37 , 57 , 58 ). Twenty-five–micrometer–thick hippocampal slices containing the CA1 region were prepared as described and labeled with Homer1 (1:1000; rabbit, Millipore, catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Two-color super-resolution imaging further reveals that mGluR4 forms nanoclusters within active zones of cerebellar PFs and co-localizes with CaV2.1 channels and Munc18 (Siddig et al, 2020 ). Similarly, presynaptic GABA B -receptors are clustered within active zones and play a critical role in regulating CaV channel function (Lujan et al, 2004 , 2018 ; Luo et al, 2021 ). By contrast, EM and super-resolution imaging show that CB1 receptors are excluded from active zones, but distributed uniformly in the extrasynaptic region of the nerve terminal (Nyiri et al, 2005 ; Dudok et al, 2015 ).…”
Section: Nanoscale Modulation Of Cav Channels By G-protein Coupled Re...mentioning
confidence: 99%
“…Primarily, Nrxs influence components of the presynaptic machinery and synaptic functional efficiency. For example, Nrx deletion results in the loss of presynaptic active-zone GABARs, decreasing the sensitivity of neurotransmitter release to GABAR activation at both excitatory and inhibitory synapses [ 22 ]. Given the importance of presynaptic GABARs in the nucleation of signaling complexes that control the release of neurotransmitters, the ability of Nrxs to regulate these receptors enables them to further govern synaptic transmission and plasticity from the presynaptic perspective [ 23 , 24 , 25 ].…”
Section: The Neurexin–neuroligin Mediated Trans-synaptic Modulationmentioning
confidence: 99%